Mission possible how the secrets of the success academies can work in any school - Moskowitz, Eva S. (Jossey-Bass, 2012)
"Strategies for making the schools we need that work for all kidsEva Moskowitz (the founder and CEO of the Success Charter Network in Harlem) and Arin Lavinia offer practical, classroom-tested ideas for dramatically improving teaching and learning. Moskowitz and Lavinia reveal how a charter school in the middle of Harlem, enrolling neighborhood children selected at random, emerged as one of the top schools in New York City and State within three years. The results of the Harlem school were on a par with public schools for gifted students and elite private schools. Describes what can be accomplished when students and adults all work to focus on constant learning and performance improvement; DVD clips are included for illustration The Success Academies have been featured in two popular and widely distributed documentaries, Waiting for Superman and The Lottery Details the Success Academies' THINK Literacy curriculum, which produces dramatic results in kids reading and writing skills In addition to providing strategies and lessons for school leaders and teachers, Secrets of the Success Academies also serves as a guide for parents, policymakers, and practitioners who are passionate about closing the academic achievement gap"--